Hydrogen Production: Iron–Titanium Oxide Nanocomposites Functionalized with Gold Particles: From Design to Solar Hydrogen Production (Adv. Mater. Interfaces 16/2016). Issue 16 (August 2016) - Barreca, Davide; Carraro, Giorgio; Gasparotto, Alberto; Maccato, Chiara; Warwick, Michael E. A.; Toniato, Elisa; Gombac, Valentina; Sada, Cinzia; Turner, Stuart; Van Tendeloo, Gustaaf; Fornasiero, Paolo
Abstract : In article 1600348, C. Maccato and co‐workers propose a low‐temperature plasma‐assisted route to supported Fe2 O3 ‐TiO2 ‐Au photocatalysts, based on the initial deposition of α‐Fe2 O3, followed by the sequential sputtering of TiO2 and Au. The intimate contact and tailored interaction between the single constituents result in highly promising H2 production yields obtained via photoreforming of water‐ethanol solutions activated by sunlight. The related insights can yield important guidelines to enhance the performances of nanostructured photocatalysts for energy‐related applications.